Molecular cloning, characterization and expression analysis of Wnt4, Wnt5, Wnt6, Wnt7, Wnt10 and Wnt16 from Litopenaeus vannamei. (July 2016) - Zhang, Shuang; Li, Chao-Zheng; Yang, Qi-Hui; Dong, Xiao-Hui; Chi, Shu-Yan; Liu, Hong-Yu; Shi, Li-Li; Tan, Bei-Ping
Abstract: The Wnt (Wg-type MMTV integration site) signaling represents as the negative regulator of virus-induced innate immune responses. Wnt genes act as ligands to activate the Wnt signaling. To know more about the information of Wnt genes in invertebrates, Litopenaeus vannamei Wnt genes (LvWnts) were identified and characterized. In this study, Six Wnt genes (LvWnt4, LvWnt5, LvWnt6, LvWnt7, LvWnt10 and LvWnt16) were obtained in L. vannamei . The complete cDNAs open reading frames (ORF) of LvWnt4, LvWnt5, LvWnt6, LvWnt7, LvWnt10 and LvWnt16 were 1077 bp, 1107 bp, 1350 bp, 1047 bp, 1509 bp and 1158 bp (GenBank accession no. KU169896, KU169897, KU169898, KU169899, KU169900 and KU169901), encoding 358, 368, 449, 348, 502 and 385 amino acid (aa) residues respectively. All the six members of LvWnts contain a Wnt1 domain, which is considered as an important feature of Wnt gene family. ClustalW analysis with amino acid sequences revealed that the proportion of identity with other species was more than 48% for all the LvWnts except LvWnt10 (36–41%). The phylogenetic relationship analysis illustrated that different subtype of Wnts formed their own separate branches and were placed in branch of invertebrates respectively with strong bootstrap support. The constitutive expressions of LvWnts were confirmed by RT-PCR in all the examined five developmental stages and eleven tissues of L. vannamei with different express patterns. LvWnt4, LvWnt5 and LvWnt10 were expressed highest in nerve while LvWnt6, LvWnt7 and LvWnt16 were expressed highest in intestine, stomach and gill, respectively. In addition, all the LvWnts were regulated by white spot syndrome virus (WSSV) challenges at different levels in hepatopancreas, gill and hemocytes, suggesting that Wnt genes may play a role in the defense against pathogenic virus infection in innate immune of L. vannamei . Highlights: Six Wnt genes were cloned from Litopenaeus vannamei . LvWnts were constitutively expressed in five developmental stages of L. vannamei . LvWnts were constitutively expressed in eleven tissues of L. vannamei . LvWnts were regulated by WSSV challenges at different levels in hemocytes, gill and hepatopancreas.